Pelatihan Pembuatan Tas Rajut untuk Meningkatkan Kemandirian Ekonomi Kreatif Komunitas Pemulung - Herdin Muhtarom; Wardah Samiah (Pusat Pengabdian kepada Masyarakat (PPKM) Universitas Prasetiya Mulya, 2025)
The economy is the main focus developed by the Indonesian government, because through an advanced economy, superior human resources will be created. But in reality the economy in Indonesia is still not optimal in its management system, this has an impact on the unemployment rate in Indonesia. In other words, there is a surplus of labor supply in the labor market. This imbalance and mismatch between job demand and job supply relies more on the creativity and intellectuals of the community in developing the existing local potential. On the other hand, the development of the creative economy in certain places is very dependent on the quality of human resources in developing the creativity of an intelligence. By implementing the creative economy in Indonesia, it is not only to overcome problems related to employment, but also relates to economic resilience, namely the dynamic conditions of the nation's economic life. By implementing the creative economy in Indonesia, it is not only to overcome problems related to employment, but also relates to economic resilience, namely the dynamic conditions of the nation's economic life. Pioneers are needed to solve problems that exist in society. One of them was carried out by PK IMM FKIP UHAMKA in the PPK ORMAWA program of the Ministry of Education and Culture in 2022 to overcome problems within the scope of the Kampung Gedong sub-district, East Jakarta through the Sopo Tresno Madrasa program to disseminate the problems that occur in the community related to ideas and ideas. creative economy development in Kampung Gedong, East Jakarta. The goal in community service is to provide education to the community in the development of the creative economy to increase economic independence in Gedong Village, East Jakarta. The community service process is carried out directly to the community since April-September in which activities continue to follow the covid-19 protocol, there are several stages that will be carried out such as: socialization at the initial stage, then from the socialization it enters the education stage about the creative economy, and the last stage analyze and provide education on the creation of knitted bags as the development of economic independence based on creativity to support economic independence